2016
DOI: 10.7554/elife.18205
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of temporal sequences in the zebra finch auditory system

Abstract: This study examines how temporally patterned stimuli are transformed as they propagate from primary to secondary zones in the thalamorecipient auditory pallium in zebra finches. Using a new class of synthetic click stimuli, we find a robust mapping from temporal sequences in the primary zone to distinct population vectors in secondary auditory areas. We tested whether songbirds could discriminate synthetic click sequences in an operant setup and found that a robust behavioral discrimination is present for clic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 47 publications
2
24
1
Order By: Relevance
“…Some studies have reported that sequences of syllables and gaps are important for vocal generation and sound recognition on social context or specificity (Araki, Bandi, & Yazaki‐Sugiyama, ; Brainard & Doupe, ; Knowles, Doupe, & Brainard, ; Lim, Lagoy, Shinn‐Cunningham, & Gardner, ; Tanaka, Singh Alvarado, Murugan, & Mooney, ; Van Ruijssevelt et al, ). In this study, the sequence of syllables and gaps corresponded to the temporal modulation of amplitude, which is correlated with neural activity in the vocal motor neurons of male birds (Danish, Aronov, & Fee, ; Lynch, Okubo, Hanuschkin, Hahnloser, & Fee, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that sequences of syllables and gaps are important for vocal generation and sound recognition on social context or specificity (Araki, Bandi, & Yazaki‐Sugiyama, ; Brainard & Doupe, ; Knowles, Doupe, & Brainard, ; Lim, Lagoy, Shinn‐Cunningham, & Gardner, ; Tanaka, Singh Alvarado, Murugan, & Mooney, ; Van Ruijssevelt et al, ). In this study, the sequence of syllables and gaps corresponded to the temporal modulation of amplitude, which is correlated with neural activity in the vocal motor neurons of male birds (Danish, Aronov, & Fee, ; Lynch, Okubo, Hanuschkin, Hahnloser, & Fee, ).…”
Section: Discussionmentioning
confidence: 99%
“…Agus Kang et al (2017) proposed that incorporating a degree of temporal integration can also account for similar effects observed with random click trains. It is possible that state-dependent neural place maps, as proposed by Kang et al (2017; see also Karmarkar & Buonomano, 2007;Lim, Lagoy, Shinn-Cunningham, & Gardner, 2017) incorporating an integration time of several hundred msec, may also underpin memory for discrete tone sequences. As will be discussed further below, the behavioural pattern reported in the present paper is consistent with sequential information being stored as short sub-sequences, i.e.…”
Section: Relationship To 'Noise Memory'mentioning
confidence: 99%
“…To simplify, spectral cues may be encoded by the place pattern of spiking rates in frequency-tuned populations of auditory neurons, whereas temporal cues may be encoded by the timing between spikes within a neuron or across neurons in a population. Even though the mapping between acoustic cues and their underlying neural representation is not wellestablished (Cariani and Delgutte, 1996;Lim et al, 2016;Shamma and Lorenzi, 2013), both place (Rothschild et al, 2010) and temporal (Lu et al, 2001;Petkov and Bendor, 2016) cues are abundant along the auditory pathways, from the auditory periphery up to at least the auditory cortex. However, the two types of cue require qualitatively different mechanisms when learning and neural plasticity are considered.…”
Section: Introductionmentioning
confidence: 99%
“…For temporal cues, however, such a mechanism does not apply directly because what needs to be learnt develops over time. So, neurons would need somehow to encode past and present information simultaneously to learn temporal patterns (Karmarkar and Buonomano, 2007;Lim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%